2015
DOI: 10.1140/epjc/s10052-015-3800-3
|View full text |Cite
|
Sign up to set email alerts
|

A new phenomenological investigation of KMR and MRW unintegrated parton distribution functions

Abstract: We address the longitudinal proton structure function, F L (x, Q 2 ), from the k t -factorization formalism by using the unintegrated parton distribution functions (UPDF) which are generated through the KMR and MRW procedures. The LO UPDF of the KMR prescription is extracted, by taking into account the PDF of Martin et al, i.e., MSTW2008-LO and MRST99-NLO, and next the NLO UPDF of the MRW scheme is generated through the set of MSTW2008-NLO PDF as the input. The different aspects of F L (x, Q 2 ) in the two app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 70 publications
(154 reference statements)
3
19
0
Order By: Relevance
“…Consequently, the overall value of the differential cross-sections of the W ± and Z 0 production in this framework reduces dramatically, as it is apparent in the figures 7 and 8 . In overall and as it has been stated elsewhere (see for example the references [27,28]) the results in the KM R scheme seemingly have a better agreement with the experiment. This is to some extend ironic, since the LO and the N LO M RW formalisms are developed as extensions and improvements to the KM R approach and are more compatible with the DGLAP evolution equation.…”
Section: Results Discussion and Conclusionsupporting
confidence: 76%
“…Consequently, the overall value of the differential cross-sections of the W ± and Z 0 production in this framework reduces dramatically, as it is apparent in the figures 7 and 8 . In overall and as it has been stated elsewhere (see for example the references [27,28]) the results in the KM R scheme seemingly have a better agreement with the experiment. This is to some extend ironic, since the LO and the N LO M RW formalisms are developed as extensions and improvements to the KM R approach and are more compatible with the DGLAP evolution equation.…”
Section: Results Discussion and Conclusionsupporting
confidence: 76%
“…As it can be seen in this figure, the result of the k t -factorization with the LO-MRW and NLO-MRW UPDFs are strangely off the data. Because, in the previous works, It was shown that the MRW UPDFs can produce the corresponding data reasonably [26][27][28][29][30][31][32][33][34], so to be sure what makes our calculation to get worse, we evaluated the differential cross section within the collinear factorization framework, using the MMHT2014nlo68cl PDFs. The prediction of the collinear factorization, as depicted in the left panel of figure 1, convinces us that there should be something wrong with this parton level event generator [3].…”
Section: A Katie Results For the Zeus Inclusive Dijet Production Datamentioning
confidence: 99%
“…Another approach for defining UPDFs is the Martin-Ryskin-Watt (MRW) approach [17,18] which assumes parton evolves according to the DGLAP evolution equations [12][13][14] till the last parton emission, and then it resums the no-emission parton probability to the hard factorization scale via the Sudakov form factor. This method is investigated in detail [19][20][21][22][23][24][25] and is shown to be successful in describing the data of different processes at the LHC, Tevatron etc [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous articles, we investigated the general behavior and stability of the KM R and M RW schemes [19][20][21][22][23][24][25][26][27]. Also, we have successfully used KM R-U P DF to calculate the inclusive production of the W and Z gauge vector bosons [28,29], the semi-N LO production of Higgs bosons [30], the production of forward-center and forward-forward di-jets [31], the prompt-photon pair production [32] and recently in the reference [33], we explored the phenomenology of the integral and the differential versions of the KM R-U P DF using the angular (strong) ordering (AOC (SOC)) constraints.…”
Section: Introductionmentioning
confidence: 99%